2019
DOI: 10.1186/s12933-019-0878-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum 1,5-anhydro-d-glucitol level on the prediction of severe coronary artery calcification: an intravascular ultrasound study

Abstract: Background A low 1,5-anhydro- d -glucitol (AG) blood level is considered a clinical marker of postprandial hyperglycemia. Previous studies reported that 1,5-AG levels were associated with vascular endothelial dysfunction and coronary artery disease (CAD). However, the association between 1,5-AG levels and coronary artery plaque in patients with CAD is unclear. Methods This study included 161 patients who underwent percutaneous coronary interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In support of our findings, 1,5-AG is reported to be a useful marker for vascular endothelial dysfunction in patients with HbA1c \ 8.0% [12]. It has also been reported that low 1,5-AG levels were associated with the severity of coronary artery calcification in patients with HbA1c \ 7.0% [32]. On the other hand, d-ROMs did not correlate with 1,5-AG in patients with HbA1c [ 8%.…”
Section: Relationship Of D-roms With Markers Of Diabetic Control and supporting
confidence: 88%
“…In support of our findings, 1,5-AG is reported to be a useful marker for vascular endothelial dysfunction in patients with HbA1c \ 8.0% [12]. It has also been reported that low 1,5-AG levels were associated with the severity of coronary artery calcification in patients with HbA1c \ 7.0% [32]. On the other hand, d-ROMs did not correlate with 1,5-AG in patients with HbA1c [ 8%.…”
Section: Relationship Of D-roms With Markers Of Diabetic Control and supporting
confidence: 88%
“…The study of Fujiwara et al showed that 1,5-AG was associated with the presence of de novo coronary artery disease in both well-controlled diabetic and non-diabetic patients [8]. Low 1,5-AG level had been found to be associated with coronary artery calcification, which may be related to the coronary plaque vulnerability [24,25]. The current study is the first to report that 1,5-AG levels are significantly associated with coronary plaque rupture in diabetic patients with ACS.…”
Section: 5-ag Levels and Coronary Plaque Rupturementioning
confidence: 97%
“…Furthermore, as PPG increments are the major contributors to GV in T2DM, 1,5-AG may be particularly suited for monitoring postprandial hyperglycemic excursions [18]. [19]. The current study is the first to report that 1,5-AG levels are significantly associated with coronary plaque rupture in diabetic patients with NSTE-ACS.…”
Section: Discussionmentioning
confidence: 63%